2015
DOI: 10.15640/jpbs.v3n1a7
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Addiction and Alexithymia

Abstract: Before presenting this investigation on exercise addiction and alexithymia, the topic of addiction is introduced by recalling a few terminological distinctions and some questions on aetiology. The investigation is focused on the relationship between alexithymia and other forms of addiction and between sporting activity and alexithymia. The sample of research consider 137 subjects attending various gyms in the city. The hypothesis are the following: 1 Existence of a correlation between alexithymia and exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…A qualitative study of male swimmers by Allegre et al (2007) suggested that expert swimmers were more alexithymic than amateur swimmers. Manfredi and Gambarini (2015) reported a positive relationship between scores on the TAS-20 and the Like alexithymia, trait impulsivity has also been linked to alcohol abuse and dependence (Littlefield & Sher, 2010), eating disorders (Beck et al, 2009;Claes et al, 2002;Kane et al, 2004) and internet addiction (Dalbudak et al, 2013;Lyvers et al, 2016;Ryu et al, 2018). Impulsivity is a multifaceted construct that Dawe et al (2004) suggested is best conceptualized in the context of substance abuse by a two-factor model, the 2-Component Approach to Reinforcing Substances (2-CARS) model (Gullo & Dawe, 2008;Gullo et al, 2010;Stautz et al, 2017), incorporating rash impulsiveness and reward drive.…”
Section: Personality Traits As Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A qualitative study of male swimmers by Allegre et al (2007) suggested that expert swimmers were more alexithymic than amateur swimmers. Manfredi and Gambarini (2015) reported a positive relationship between scores on the TAS-20 and the Like alexithymia, trait impulsivity has also been linked to alcohol abuse and dependence (Littlefield & Sher, 2010), eating disorders (Beck et al, 2009;Claes et al, 2002;Kane et al, 2004) and internet addiction (Dalbudak et al, 2013;Lyvers et al, 2016;Ryu et al, 2018). Impulsivity is a multifaceted construct that Dawe et al (2004) suggested is best conceptualized in the context of substance abuse by a two-factor model, the 2-Component Approach to Reinforcing Substances (2-CARS) model (Gullo & Dawe, 2008;Gullo et al, 2010;Stautz et al, 2017), incorporating rash impulsiveness and reward drive.…”
Section: Personality Traits As Risk Factorsmentioning
confidence: 99%
“…A minority of those who exercise regularly may become psychologically dependent on exercise and exhibit symptoms similar to addictions such as craving, impaired control, tolerance, withdrawal, engaging in the behavior despite negative consequences such as injuries, and interference with other life domains (Hausenblas & Symons Downs, 2002a). A review by Sussman et al (2011a) concluded that the prevalence rate of exercise dependence in the general population is approximately 3%, though a prevalence of nearly 9% was reported in a sample of gym attendees (Manfredi & Gambarini, 2015). As a relatively new concept, exercise dependence has also been referred to as exercise addiction, obsessive exercise, compulsive exercise, exercise abuse, obligatory exercise and problematic practice of physical exercise (Egorov & Szabo, 2013).…”
mentioning
confidence: 99%
“…The relationship between alexithymia and exercise addiction has been examined in different populations of exercisers, such as those attending fitness centers [24], swimmers [25], and sports university students [26]. Some research has suggested that the use of physical activity could be a means by which these individuals try to suppress their unmentalized emotional states, as a form of dissociation from painful experiences [17,24].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between alexithymia and exercise addiction has been examined in different populations of exercisers, such as those attending fitness centers [24], swimmers [25], and sports university students [26]. Some research has suggested that the use of physical activity could be a means by which these individuals try to suppress their unmentalized emotional states, as a form of dissociation from painful experiences [17,24]. An interesting point of view is provided by some research arguing that the inability to symbolize emotional experiences-as well as the resulting undifferentiated and dysregulated affect-may also lead to body image distortion [27].…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral psychology is a psychology that put forward behavior as their core. Because of that, this psychology focused on the effect of changes and stimulus that been created by the environment as the study medium [4]; [8]; [17]. This psychology is well known as a theory of stimulus respond and in the modern era it is well known by the academician who are focused in environment.…”
Section: Introductionmentioning
confidence: 99%